2015
DOI: 10.7763/ijet.2015.v7.790
|View full text |Cite
|
Sign up to set email alerts
|

Developing Master Curves, Binder Viscosity and Predicting Dynamic Modulus of Polymer-Modified Asphalt Mixtures

Abstract: Abstract-The complex moduli relationship related mixture moduli to temperature and time rate of loading has been an integral part of several mechanistic-empirical (M-E) design procedures used throughout of the world. Seven asphalt concrete mixtures of different types of polymer modified binders (PMB) were produced in a laboratory to modify performance of asphalt mixture. The main role of this research is to evaluate the influence of these polymer modifiers on the pavement performance of asphalt mixture with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Polymers also have relatively low permeability. Among the various modifiers, polymer additives were found to be particularly effective because they demonstrate enhanced performance by increasing binder stiffness at elevated temperatures while preserving flexibility at low temperatures [9][10][11][12]. Polymer-modified asphalts exhibit enhanced resistance to thermal cracking and rutting, as well as reduced fatigue damage, temperature sensitivity, and stripping [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Polymers also have relatively low permeability. Among the various modifiers, polymer additives were found to be particularly effective because they demonstrate enhanced performance by increasing binder stiffness at elevated temperatures while preserving flexibility at low temperatures [9][10][11][12]. Polymer-modified asphalts exhibit enhanced resistance to thermal cracking and rutting, as well as reduced fatigue damage, temperature sensitivity, and stripping [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Among the different tested modifiers, polymer additives were found significantly functional due to their perceived superior performance, as they increase the stiffness of binders at high temperatures while upholding flexibility at lower temperatures. [10][11][12][13] Polymer-modified asphalts (PMAs) shows greater resistance to thermal cracking and rutting, as well as reduced fatigue damage, temperature susceptibility, and stripping. [14][15][16][17][18] PMAs are typically produced by mixing asphalt binder with 3% to 7% polymer additive by weight through mechanical dispersion under high shear.…”
Section: Introductionmentioning
confidence: 99%
“…Various types of modifiers have been tested by researchers to mitigate the distress associated with the behavior of conventional asphalt binders [1][2][3][4]. Many researchers concluded that the asphalt binder modification increased the complex modulus of bitumen at high temperatures while reducing it at low temperatures [5][6][7][8][9]. Also, the bitumen modifier shows high resistance to thermal cracking, rutting, and…”
mentioning
confidence: 99%